Fatty Acid Composition in Ten Mushroom Species Collected from Middle Black Sea Region of Turkey - Yilmaz, Necmettin; Turkekul, Ibrahim; Bulut, Sait; Sahin, Fikrettin; Faruk Bayrak, O. (Asian Journal of Chemistry, 2012)
The aim of this study was to determine the amount and composition of fatty acids in 10 edible mushroom species, which belongs to Trichomataceae, Plourotaceae, Clavariaceae, Cantharellaceae, Agaricaceae, Strophariaceae, Lepiotaceae, Russsulaceae familials grown in the middle black sea region (Tokat, Amasya, Ordu provinces). The amount and composition of fatty acids in dried mushrooms samples were detected by a gas chromatography. The fatty acids were determined using the fatty acids methyl-esters standards. Fatty acids with 9-24 carbons were found in mushrooms samples. Also, fatty acids with a single carbon and single double-bound were found. Linoleic acid (18:2 w 6c) occurred greater than 50 % in most of the samples studied. Fatty acid analysis of the mushroom in the present study showed that unsaturated fatty acids were higher than the saturated ones.